Comunicação e imagem organizacional: um estudo de suas relações no comércio varejista de shopping centers - Souza, Karlla Kathyane Galdino de (2006)
This study shows the results of an exploratory-descriptive research that aimed to identify the latent dimensions of communication, as well as finding relations between such dimensions and organizational image. The sample came to a total of 267 respondents, being 89 managers or owners and 178 salespeople of clothing and footwear stores that are situated in the main five shopping centers located in Natal, capital of Rio Grande do Norte. The collection of the data was made by the use of two structuralized and validated instruments, being the answers measured in the likert scale of 6 points. For the measurement of communication it was used the instrument developed by Downs and Hazen (2002), made up of 8 latent dimensions and 32 indicators. For the image it was used the model of Mael and Ashforth (1992) that contains 5 indicators. The analysis of the data was made through of the use of statistical techniques of factorial analysis and structural equations modeling. The results of the factorial analysis demonstrated communication as being formed by five latent dimensions. The modeling, on the other hand, demonstrated to exist positive relations between communication and organizational image, whose results revealed that the image is influenced by the communication with the supervisor, by the organizational integration and as being stronger explained by the vertical communication